PERAN MAHKAMAH KONSTITUSI DALAM PENYELESAIAN SENGKETA PEMILU 2009 - Arsil, Fitra (Jurnal Legislasi Indonesia, 2009)
The Constitutional Court has played a major and decisive rolein the last election in 2009. Major role has even begun longbefore the general election phase began to be implemented andthe end of the election stage is also determined by the role ofthe Constitutional Court. Role of the Constitutional Court is notlimited to law enforcement types contained in the Act governingthe elections, namely the dispute over the result but much biggerthan that. Interestingly, in performing its role the Court hasissued decisions controversy that has never previouslyencountered, even the decision of the Court authority alsointersecting with other judicial institutions. But on the other sideis also found in guarantees of citizens rights and minimalprotection can actually be done by the Constitutional Court.Election 2009 also suggests that institutions like theConstitutional Court that can act as a determinant of a verydelicate political process that could drag the politicization ofthis institution out of the originality.